Phase equilibria in the Na,Ca//SO4,CO3,HCO3-H2O system at 0 °C - L. Soliev; M. T. Jumaev (Chimica Techno Acta)
Phase equilibria in the Na,Ca//SO4,CO3,HCO3-H2O system have been studied at 0 °C. The studied system at 0 °C involves 4 invariant points, 13 monovariant curves and 15 divariant fields. The obtained results served as a basis for the construction of phase diagram (phase complex) of the studied system at 0 °C.